Globalisation of Research and Development of the World’s Top Corporate R&D Investors - Heike Belitz; Anna Lejpras (Wirtschaftsdienst)
Abstract Patent data from the world’s top corporate R&D investors can be used to generate information on the regional and technological distribution of their research activities. This provides clues about the motives for internationalisation. Companies conduct R&D abroad predominantly in technological fields where they have a domestic advantage and the foreign location has advantages. The most important home countries of research-based companies are also the most important target countries for research abroad. Thus, both the companies and the research locations are likely to benefit from the internationalisation of R&D.